Creating a map of Arctic Indigenous languages and revitalization - Nordström, Linnea (Septentrio Conference Series, 2021)
In 2019 the University Library at UiT - The Arctic University of Norway partnered with the Arctic Council Indigenous Peoples' Secretariat to create Ságastallamin - Telling the Story of Arctic Indigenous Languages, an interactive multi-media exhibition commemorating the UN International Year of Indigenous Languages. An Arctic Indigenous language map was updated for use in the exhibition, but the print format proved to be limiting, and the exhibition time frame did not allow for a thorough linguistic review. Therefore a follow-up project “Arctic Indigenous languages and revitalization: an online educational resource” was started in 2021 to further develop the map and convert it to an openly available online educational resource in GIS format. One key aspect of the new map is that it will feature individual language names in their Indigenous names, as well as in English and Russian. The project team consists of representatives from Higher Educational Institutions, Indigenous organizations, and Government departments from Canada, Finland, Greenland, Norway, Russia and the United States. The work on the map has just begun and this spring and summer the goal is to collect feedback from Indigenous language experts on the original exhibition print map before designing a new GIS version in the fall. We would like to present the current print map to the Arctic Knot conference in order to receive feedback about additional languages to include, creative ways to present language information in different layers, and suggestions for innovative language revitalization initiatives to feature on the map. There is an online form to collect feedback, and so the lightning talk would be used to present the project goals briefly and then encourage conference participants to submit feedback using the form after the talk.